PENGEMBANGAN ALAT BANTU REHABILITASI PASIEN PASCASTROKE BERBASIS VIRTUAL REALITY - , KRISTANTO AGUNG NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Stroke is a disease that is deadly because it can cause disability and death in patients. Disabled patients should do exercises regularly repeated in order to recover back to normal. Unfortunately workout repeatedly can cause boredom for patients. When a patient to train what became their favourite, then the recovery process will feel like playing because of patient flow through a phase. Phase flow is very often encountered when a person plays a virtual reality (VR) is often called a non-immersive video games or more short game. Therefore the developed toolbased rehabilitation for post-stroke patientâs virtual reality using Kinect in the form of a game with the aim to cause the patient may experience a feeling of flow. Game development begins with determining the needs of the consumer attributes from interviews and observations. Next step is the preparation of product specifications to obtain the type of movement, duration, variations in the level of difficulty of movement rehabilitation, and game materials are in accordance with the needs of the patient and physiotherapist. The next process is done by making several game concepts that can be developed, and then make a selection and assessment to determine the concept of decent games to be developed. The concept that has been selected to be the concept then made a prototype. The prototype consists of a prototype made of paper, digital prototypes and storyboards. Further testing on the prototype. The result is a game Jaka Sembuh. Game consists of programming code and graphical user interface (GUI) to assist the rehabilitation of the upper limb patients. Game has dramatic elements, namely: challenge, play, premise, characters and story. Usability and flow testing showed that the games that have been made can be used to assist in the rehabilitation properly. Keywords: stroke, rehabilitation, flow, virtual reality, gaming